Modified graphene microchip, preparation method and application

By intercalating and grafting maleic anhydride on the surface of graphene, the problem of poor compatibility of graphene with resin and solvent is solved, and the mechanical, thermal and electrical conductivity of composite materials is significantly improved.

CN119503783APending Publication Date: 2025-02-25XIAMEN KNANO GRAPHENE TECH CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411485937.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The surface polarity of graphene is insufficient, resulting in poor compatibility with resins, solvents, etc., affecting the mechanical properties, thermal conductivity and electrical conductivity of composite materials.

Method used

By stirring maleic anhydride with expanded graphite or worm graphite and reacting with liquid peroxygen initiator, heated in vacuo to generate gas peeling to form maleic anhydride grafted graphene microsheets to improve its surface polarity.

Benefits of technology

The compatibility of graphene microsheets with resins, solvents, etc. is improved, and the mechanical properties, thermal conductivity and electrical conductivity of composite materials are synergistically improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005098706210000091
    Figure BDA0005098706210000091
  • Figure BDA0005098706210000101
    Figure BDA0005098706210000101
  • Figure BDA0005098706210000102
    Figure BDA0005098706210000102
Patent Text Reader

Abstract

The invention relates to the technical field of carbon materials, in particular to a modified graphene microchip and a preparation method and application thereof.The preparation method comprises the steps that S1, maleic anhydride and expanded graphite or worm graphite are stirred and mixed, and a first premix is obtained after cooling; s2, stirring and mixing the first premix with a liquid peroxide initiator to obtain a second premix; and S3, heating the second premix in vacuum and reacting for a certain time, and cleaning and crushing to obtain the modified graphene nanoplatelets. According to the preparation method, maleic anhydride is intercalated and grafted to expanded graphite or vermicular graphite in a low-cost environment-friendly manner, and the expanded graphite or vermicular graphite is stripped by utilizing gas generated by reaction to obtain the maleic anhydride grafted graphene nanoplatelets, so that the surface polarity of the graphene nanoplatelets is greatly improved, and the compatibility of the graphene nanoplatelets with resin, a solvent and the like is effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of carbon materials, and in particular to a modified graphene microsheet, a preparation method and an application thereof. Background Art

[0002] Graphene has a perfect structure and few surface functional groups, which makes it excellent in electrical and thermal conductivity. However, graphene is neither hydrophilic nor oleophilic, and has poor compatibility with resins, organic solvents or inorganic solvents. For example, when mixed with resin, the composite material is easy to delaminate, the surface is rough, and it is difficult to disperse. In conductive or thermal conductive slurries, graphene has poor compatibility with solvents and the slurry is easy to delaminate. Therefore, even if graphene has excellent electrical and mechanical properties, it is difficult to improve the effect in practical applications. Summary of the invention

[0003] In view of the above problems in the prior art, the present application provides a modified graphene microsheet, a preparation method and an application thereof, and the specific technical scheme is as follows:

[0004] On the one hand, the present application provides a method for preparing a modified graphene microplatelet, the preparation method comprising:

[0005] S1: stirring and mixing maleic anhydride and expanded graphite or vermicular graphite, and cooling to obtain a first premix;

[0006] S2: stirring and mixing the first premix with a liquid peroxygen initiator to obtain a second premix;

[0007] S3: heating the second premix in a vacuum and reacting it for a certain period of time, and then washing and crushing it to obtain modified graphene microsheets.

[0008] In a possible implementation, S1 includes: preheating a high-speed mixer to 45° C.-51° C., adding maleic anhydride and expanded graphite or worm graphite, stirring at high speed, taking out and cooling, to obtain the first premix.

[0009] In a possible implementation manner, the stirring time in S1 is 15-25 min.

[0010] In a possible implementation manner, the mass ratio of maleic anhydride to expanded graphite or worm-shaped graphite in S1 is 20:100-40:100.

[0011] In a possible implementation manner, the mass ratio of the liquid peroxygen initiator to the expanded graphite or the worm graphite is 7:100-15:100.

[0012] In a possible implementation manner, the reaction temperature in S2 is room temperature.

[0013] In a possible implementation manner, the temperature of heating S3 in vacuum is 90-110° C., and the reaction time is 20-26 h.

[0014] In a possible implementation manner, the liquid peroxy initiator includes one or more of tert-butyl peroxide-2-ethylhexanoate, di-tert-butyl peroxide, tert-butyl perbenzoate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, and 2,5-dimethyl-2,5-bis(tert-butylperoxide)-3-hexyne.

[0015] On the other hand, the present application provides a modified graphene microsheet, which is prepared by the preparation method as described above.

[0016] On the other hand, the present application provides an application of the modified graphene microsheets prepared by the preparation method as described above in thermal conductive materials and / or conductive materials.

[0017] In another aspect, the present application provides a method for preparing a thermally conductive material, the method comprising:

[0018] Providing a modified graphene microsheet prepared by the preparation method as described above;

[0019] The modified graphene microsheets are mixed with a plastic matrix material for granulation to obtain a modified graphene microsheet plastic composite material.

[0020] Based on the above technical solution, this application has the following beneficial effects:

[0021] The present application adopts a low-cost and environmentally friendly method to intercalate and graft maleic anhydride onto expanded graphite or worm-like graphite, and utilizes the gas generated by the reaction to exfoliate the expanded graphite or worm-like graphite to obtain maleic anhydride-grafted graphene microsheets, thereby greatly improving the surface polarity of the graphene microsheets, effectively improving their compatibility with resins, solvents, etc., and thereby synergistically improving the mechanical properties, thermal conductivity and electrical conductivity of the composite material. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0023] For the following defined terms, these definitions shall apply unless a different definition is given in the claims or elsewhere in this specification. All numerical values, whether or not explicitly indicated, are defined herein as modified by the term "about". The term "about" generally refers to a numerical range that a person of ordinary skill in the art considers to be equivalent to the stated values ​​to produce substantially the same properties, functions, results, etc. A numerical range indicated by a lower value and a higher value is defined to include all numerical values ​​included in the numerical range and all subranges included in the numerical range.

[0024] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions.

[0025] The following describes the preparation method of the modified graphene microsheet provided in the embodiment of the present application. This specification provides the method operation steps as in the embodiment, but may include more or fewer operation steps based on conventional or non-creative labor. The order of steps listed in the embodiment is only one way of executing the order of many steps and does not represent the only execution order. When the preparation method is actually executed, it can be executed in the order of the method shown in the embodiment or in parallel. The preparation method includes S1-S3:

[0026] S1: stirring and mixing maleic anhydride and expanded graphite or vermicular graphite, and cooling to obtain a first premix;

[0027] S2: stirring and mixing the first premix with the liquid peroxygen initiator to obtain a second premix;

[0028] S3: heating the second premix in a vacuum and reacting it for a certain period of time, and then washing and crushing it to obtain modified graphene microsheets.

[0029] Specifically, after maleic anhydride is fully mixed with expanded graphite or worm graphite, the surface of the expanded graphite or worm graphite can be at least partially covered by maleic anhydride, and then after being fully mixed with a liquid peroxy initiator, a grafting reaction is initiated at a certain temperature. In this process, maleic anhydride and an excess of peroxy initiator are intercalated into the expanded graphite or worm graphite, and the small molecule gas generated by the reaction promotes the peeling of the expanded graphite or worm graphite, and the formed graphene micro-sheets are further contacted with maleic anhydride and an excess of peroxy initiator and reacted and grafted to obtain modified graphene micro-sheets with good surface modification. The above method allows low-cost expanded graphite or worm graphite to directly form grafted graphene micro-sheets through a one-step reaction, has high reaction efficiency and simplified steps, is conducive to large-scale production, and does not require an acidic stripping agent or other organic solvents in the process, and the product is simple to clean, efficient and environmentally friendly.

[0030] It can be understood that the strong polar groups of maleic anhydride grafted on graphene microsheets can serve as a bridge between graphene microsheets and other materials, such as being effectively compatible with materials such as plastic matrices to obtain strong bonding with other materials such as plastic matrix resins, avoid material stratification, and improve mechanical properties such as toughness and surface smoothness of materials. They can be applied to thermally conductive or electrically conductive materials to improve the thermal conductivity and / or electrical conductivity of materials. Moreover, the modified graphene microsheets prepared by the above method do not need to use organic solvents or dispersants when compounding with other materials. The process is environmentally friendly and the compounding process is simple, which is particularly suitable for large-scale industrial production.

[0031] In some embodiments, S1 may specifically include: preheating a high-speed mixer to 45°C-51°C, adding maleic anhydride, and expanded graphite or worm graphite, stirring at high speed, taking out and cooling, and obtaining a first premix. The above method directly uses powder mixing to add materials, does not require solvent components such as organic solvents, and the process is environmentally friendly. The preheating temperature is slightly lower than the melting point of maleic anhydride, and the maleic anhydride can be quickly softened under the preheating effect, easy to stir, and reach the melting point under the stirring heat generation effect to fully mix and contact with the expanded graphite or worm graphite, so as to achieve uniform coating and avoid wall sticking, improve premixing efficiency and avoid material waste.

[0032] In some embodiments, the stirring time in S1 is 15-25 min, preferably 20 min. By adding maleic anhydride and expanded graphite or worm graphite after preheating, the premixing time can be effectively reduced and the reaction efficiency can be improved.

[0033] In some embodiments, the stirring speed used in S1 is 500-3000 rpm, preferably 1000-2000 rpm. In this way, the uniform coating and sufficient contact of maleic anhydride on the surface of expanded graphite or worm graphite are ensured, which is beneficial to the subsequent intercalation and addition grafting reactions.

[0034] In some embodiments, the mass ratio of maleic anhydride to expanded graphite or worm graphite in S1 is 20:100-40:100, and can be any point value within the above range such as 20:100, 25:100, 30:100, 35:100, 40:100, etc., which are not enumerated here, and are preferably 30:100. By adding an excess of maleic anhydride in the above proportion, the intercalation success rate and grafting rate of maleic anhydride and peroxy initiator can be effectively increased, and at the same time, the problem of excessive side reaction products caused by excessive addition can be avoided, so that the modified graphene microsheet product can reach the required thickness and grafting rate, and is then suitable for compounding with materials such as plastic matrices.

[0035] In some embodiments, the reaction temperature in S2 is room temperature, and the use of a liquid peroxy initiator can achieve blending at room temperature, thereby reducing the difficulty of mixing and improving the mixing uniformity.

[0036] In some embodiments, the stirring time in S2 is 3-6 min, preferably 5 min. By adding a liquid peroxy initiator and premixing maleic anhydride with expanded graphite or worm graphite, the stirring time can be shortened while lowering the mixing temperature, thereby effectively improving the reaction efficiency.

[0037] In some embodiments, S2 may specifically include: pouring the first premix into another high-speed mixer at room temperature, then adding an excess of liquid peroxy initiator, stirring at high speed for 3-6 minutes, and taking out to obtain a second premix.

[0038] In some embodiments, the stirring speed used in S2 is 500-3000 rpm, preferably 1000-2000 rpm. In this way, the uniform mixing and sufficient contact between the liquid peroxy initiator, maleic anhydride, and expanded graphite or worm graphite are ensured, which is beneficial to the subsequent intercalation and addition grafting reactions.

[0039] In some embodiments, the liquid peroxy initiator includes one or more of tert-butyl peroxide-2-ethylhexanoate, di-tert-butyl peroxide, tert-butyl peroxybenzoate, 1,1-bis(tert-butyl peroxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butyl peroxy)cyclohexane, and 2,5-dimethyl-2,5-bis(tert-butyl peroxide)-3-hexyne. By using the above peroxy initiators, it can be uniformly adhered to the surface of expanded graphite or worm graphite, and is not easy to volatilize during baking.

[0040] In some embodiments, the mass ratio of the liquid peroxygen initiator to the expanded graphite or the worm graphite is 7:100-15:100, specifically, it can be any point value within the above range such as 7:100, 8:100, 10:100, 12:100, 15:100, etc., which are not enumerated here, and preferably 10:100. By adding an excess of liquid peroxygen initiator and controlling the amount to the above range, effective intercalation exfoliation and grafting of the expanded graphite or the worm graphite can be achieved, avoiding the problem of insufficient exfoliation caused by too low an amount added, and avoiding the problem of too high an amount added causing the graphene microsheet product to be too thin and unsuitable for composite with other materials.

[0041] In some embodiments, the second premix can be placed in a vacuum oven for reaction, and the temperature of S3 heating in vacuum is 90-110°C, and the reaction time is 20-26h. Specifically, the heating temperature can be any point value of 90-110°C, and the reaction time can be any point value of 20-26h. Preferably, the heating temperature is 100°C and the reaction time is 24h. By controlling the above reaction temperature and reaction time, maleic anhydride, peroxy initiator, and expanded graphite or worm graphite can be fully reacted, and gas generation can be accelerated to exfoliate expanded graphite or worm graphite. In some embodiments, the small molecule gas generated during the grafting reaction is carbon dioxide.

[0042] Specifically, after the reaction is completed, the product is washed with water to remove unreacted maleic anhydride, reaction byproduct polymaleic anhydride and excess initiator, filtered and dried, and then subjected to primary and secondary crushing to obtain a modified graphene microsheet product.

[0043] In some embodiments, during the heating of the second premix in a vacuum environment, the second premix is ​​placed in a closed and vacuum reaction vessel to enhance the contact between the small molecule gas and the expanded graphite or worm-shaped graphite during the reaction, thereby enhancing the exfoliation effect of the expanded graphite or worm-shaped graphite and the grafting effect of the graphene microsheets.

[0044] In summary, through the one-step intercalation and exfoliation coordinated grafting reaction, a graphene microsheet material with high purity, high crystallinity, excellent electrical and mechanical properties is obtained. The graphene structure is complete and has few defects, so that it can be well combined with resins such as nylon or polycarbonate, as well as polar solvents such as water, dimethylformamide and N-methylpyrrolidone.

[0045] The thermally conductive material or the electrically conductive material obtained by adding the graphene nanosheets has excellent mechanical properties and thermal conductivity, and the preparation of the modified graphene nanosheets is environmentally friendly and low-cost, and is particularly suitable for industrial mass production.

[0046] Specifically, the average thickness of the modified graphene microsheets prepared by the above method is 20-200nm, preferably 40-100nm. By controlling the content of each component in the preparation method and the corresponding reaction conditions, the product thickness can be made within the above range to be suitable for compounding with materials such as resins, thereby increasing the addition amount at a low cost, improving product performance while reducing the impact on material fluidity and mechanical properties.

[0047] In a possible implementation manner, the average diameter of the graphene microsheets used is 50-300 μm, preferably 80-200 μm; the diameter of the modified graphene obtained is 40-280 μm.

[0048] In some embodiments, the grafting rate of the prepared modified graphene microsheets is 3-8%.

[0049] The present application also provides an application of the modified graphene microsheets prepared by the above preparation method in thermal conductive materials. The modified graphene microsheets are mixed with resin matrix materials as additives to obtain a composite thermal conductive material of resin material and grafted graphene, which has excellent mechanical properties and thermal conductivity.

[0050] The present application also provides a method for preparing the above-mentioned thermal conductive material, which specifically comprises: providing modified graphene microsheets obtained by the above-mentioned preparation method; mixing and granulating the modified graphene microsheets with a resin matrix material to obtain a modified graphene microsheet plastic composite material.

[0051] The resin matrix material includes but is not limited to nylon 6, polycarbonate, etc. The resin matrix and the modified graphene microsheets can be mixed in a high-speed mixer and added into a twin-screw extruder for mixing and granulation.

[0052] In some embodiments, the temperature of the extruder is set to 250-270° C., and the screw speed is 100-300 rpm.

[0053] In some embodiments, the mass ratio of the modified graphene microplatelets to the resin matrix material is 10:90 to 80:20, preferably 40:60 to 50:50.

[0054] This application uses modified graphene microsheets as an additive material to ensure that graphene and plastic resin matrix materials are bridged by means of maleic anhydride groups, which greatly improves the combination of physical graphene and matrix resin / solvent, and does not require the addition of maleic anhydride during the extrusion granulation process, thereby solving the problem of poor toughness of high thermal conductivity plastic composite materials, and obtaining composite thermal conductive materials with excellent mechanical properties and thermal conductivity and smooth surface, with low preparation cost and environmentally friendly process. The thermal conductivity of the prepared thermal conductive material measured perpendicular to the product plane can reach more than 5W / (m·K), and the thermal conductivity of the material obtained by the measurement method parallel to the surface can reach more than 50W / (m·K).

[0055] The following describes specific embodiments of the present application in combination with the above-mentioned modified graphene microsheets, preparation methods and applications.

[0056] The preparation methods of the modified graphene microsheets and thermally and electrically conductive materials in Examples 1-7 and Comparative Examples 1-4 include the following steps:

[0057] Preparation of modified graphene microsheets:

[0058] (1) heating a high-speed mixer to 50° C., pouring m1 kg of maleic anhydride and m2 kg of expanded graphite (or worm graphite), stirring at high speed for 20 min, taking out the material and cooling it to obtain a first premix;

[0059] (2) pouring the first premix into another high-speed mixer at room temperature, then adding m3 kg of liquid peroxy initiator and stirring at high speed for 5 minutes to obtain a second premix;

[0060] (3) Then put it into a vacuum oven, evacuate it, and react at a temperature of 100°C for 24 hours. During this process, maleic anhydride and excess peroxy initiator are intercalated into expanded graphite or worm graphite. The carbon dioxide produced by the reaction promotes the exfoliation of expanded graphite (or worm graphite), thereby forming expanded graphite (or worm graphite) intercalated with maleic anhydride. The expanded graphite (or worm graphite) is rinsed and filtered with water to remove unreacted maleic anhydride, reaction by-product polymaleic anhydride, and unreacted excess liquid peroxy initiator, thereby obtaining modified graphene microsheets.

[0061] The mass of each component and the performance parameters of the modified graphene microsheets are shown in Tables 1 and 2.

[0062] Preparation of thermally or electrically conductive materials:

[0063] The modified graphene microsheets obtained in step (3) and nylon 6 are mixed with a high-speed mixer, and then added into a twin-screw extruder for mixing and granulation. The temperature of the extruder is set to 250-270° C. and the screw speed is 100-300 rpm to obtain a thermally conductive or electrically conductive material of nylon and modified graphene microsheets.

[0064] The relevant parameters of the above embodiments and comparative examples are shown in Table 1 below, and the relevant performance test results of the prepared materials are shown in Table 2.

[0065] Table 1

[0066]

[0067]

[0068] Table 2

[0069]

[0070]

[0071] Based on the above Table 1 and Table 2, it can be seen that the mass ratio between maleic anhydride and expanded graphite (or worm graphite) and the mass ratio between peroxy initiator and expanded graphite (or worm graphite) set in the present application make the mechanical properties and thermal conductivity of the material well balanced, and the density of the obtained thermally conductive or electrically conductive material reaches more than 1.48g / cm3, the tensile strength reaches more than 60Mpa, the elongation at break is more than 2%, the flexural strength reaches more than 75Mpa, the flexural modulus is more than 11110, the notched impact strength is more than 5.2KJ / m2, the thermal conductivity is more than 8W / m·K, and the surface resistance can reach less than 103. In addition, referring to the comparative example data, it can be seen that too little maleic anhydride will cause the grafting rate to be too low (Comparative Example 1), the effect of reinforcing the combination of plastic and graphite is not good, and the mechanical properties are affected, while too much maleic anhydride (Comparative Example 2) will cause more small molecules to remain, hinder the thermal diffusion performance and thus cause poor thermal conductivity, and reduce the electrical conductivity. Furthermore, if the initiator is too little (Comparative Example 3), the intercalation effect is too weak and the expansion multiple is small, resulting in low thermal conductivity of the filler and poor thermal conductivity of the material; if the initiator is too much (Comparative Example 4), there will be too much residue, resulting in a decrease in mechanical properties.

[0072] The above description has fully disclosed the specific implementation methods of the present application. It should be pointed out that any changes made by technicians familiar with the field to the specific implementation methods of the present application do not deviate from the scope of the claims of the present application. Accordingly, the scope of the claims of the present application is not limited to the above specific implementation methods.

Claims

1. A method for preparing a modified graphene microsheet, characterized in that: The preparation method comprises: S1: stirring and mixing maleic anhydride and expanded graphite or vermicular graphite, and cooling to obtain a first premix; S2: stirring and mixing the first premix with a liquid peroxygen initiator to obtain a second premix; S3: heating the second premix in a vacuum and reacting it for a certain period of time, and then washing and crushing it to obtain modified graphene microsheets.

2. The preparation method according to claim 1, characterized in that: S1 includes: Preheat the high-speed mixer to 45° C.-51° C., add maleic anhydride and expanded graphite or worm graphite, stir at high speed, take out and cool to obtain the first premix.

3. The preparation method according to claim 1, characterized in that: The stirring time in S1 is 15-25 min.

4. The preparation method according to claim 1, characterized in that: The mass ratio of maleic anhydride to expanded graphite or worm-shaped graphite in S1 is 20:100-40:

100.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the liquid peroxygen initiator to the expanded graphite or the worm graphite is 7:100-15:

100.

6. The preparation method according to claim 1, characterized in that: The reaction temperature in S2 is room temperature.

7. The preparation method according to claim 1, characterized in that: The heating temperature of S3 in vacuum is 90-110°C, and the reaction time is 20-26h.

8. The preparation method according to claim 1, characterized in that: The liquid peroxy initiator comprises one or more of tert-butyl peroxide-2-ethylhexanoate, di-tert-butyl peroxide, tert-butyl peroxybenzoate, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, and 2,5-dimethyl-2,5-bis(tert-butylperoxide)-3-hexyne.

9. A modified graphene microsheet, characterized in that: The method is prepared according to any one of claims 1 to 8.

10. Use of the graphene microplatelet according to claim 9 in thermal conductive materials and / or conductive materials.

Citation Information

Patent Citations

  • Polypropylene / montmorillonite / graphite nanocomposite material and preparation method for same

    CN103360678A

  • Heat-conductive flame-retardant polyvinyl chloride composite material and preparation method thereof

    CN109294123A

  • Preparation method of flame-retardant polyamide composite material

    CN112341804A

  • Furniture skin-touch decorative film and preparation method thereof

    CN116496524A

  • Fabrication method of toughened pa

    EP3081585A1